Applications of planar microfluidic devices and gas chromatography for complex problem solving. Issue 1 (4th December 2012) - Luong, Jim; Gras, Ronda; Shellie, Robert A.; Cortes, Hernan J.; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The application of planar microfluidic devices in GC for the separation of components of interest otherwise difficult to separate in a single analysis is presented. A variety of configurations were used for parallel chromatography, column effluent splitting, back flushing, selectivity tuning, valve less switching and column isolation, heart cutting, and comprehensive multidimensional chromatography. The synergies of recently commercialized planar microfluidic devices combined with the resolving power of fused‐silica capillary columns are demonstrated. Difficult separations were accomplished in one single analysis, such as light hydrocarbons in air with high‐moisture content, fixed gases in hydrocarbons, trace sulfur containing compounds in natural gas, and oxygenated compounds in hydrocarbons, among others.